2015
DOI: 10.21909/sp.2015.02.690
|View full text |Cite
|
Sign up to set email alerts
|

Personal Need for Structure, Anxiety, Selfefficacy and Optimism

Abstract: Abstract:The aim of the study is to contribute to the explanation of mutual relations between personal need for structure, anxiety, optimism and self-efficacy. The research sample comprised 237 university students (men n = 48 and women n = 189). The following instruments were administered: Personal Need for Structure (PNS), Spielberger's Trait Personality Inventory (STPI), Generalized Self-Efficacy Scale (GSES) and Life Orientation Test -Revised (LOT-R). Significant differences between men and women in their P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…In particular, the optimism that reflects a positive outlook and orientation toward the future (Carver, Scheier, & Segerstrom, 2010) seems to be a pivotal factor in adapting to transitions (Stanojević, Krstić, Jaredić, & Dimitrijević, 2014). Earlier studies indicated the predictive power of optimism over career adaptability (Buyukgoze-Kavas, 2014Rottinghaus, Day, & Borgen, 2005), and Ochoa (2011) and Prokopcáková (2015) have characterized higher optimism and higher self-efficacy as positive resources for acting in flexible ways.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the optimism that reflects a positive outlook and orientation toward the future (Carver, Scheier, & Segerstrom, 2010) seems to be a pivotal factor in adapting to transitions (Stanojević, Krstić, Jaredić, & Dimitrijević, 2014). Earlier studies indicated the predictive power of optimism over career adaptability (Buyukgoze-Kavas, 2014Rottinghaus, Day, & Borgen, 2005), and Ochoa (2011) and Prokopcáková (2015) have characterized higher optimism and higher self-efficacy as positive resources for acting in flexible ways.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported in the literature (Barnett, & Adams, 2018;Ey et al, 2005;Räikkönen, Matthews, Flory, Owens, & Gump, 1999;Rajandram et al, 1999;Siddique et al, 2006;Singh, & Jha, 2013;Warning, 2011). In his comparative study, Prokopcáková (2015) found that the trait anxiety scores of the university students with low optimism scores (pessimist) are high and that those who have low anxiety levels have high optimism scores.…”
Section: Findings Discussion and Conclusionmentioning
confidence: 99%
“…Adicionalmente, son diversos los factores -entre ellos, los sociodemográficos-que pueden interferir en la CVL y la AEP. Por ejemplo, se reportaron mayores puntuaciones de autoeficacia en los hombres en comparación con las mujeres (Covarrubias y Mendoza, 2016;Prokopcáková, 2015), aunque otros resultados señalan mayores puntuaciones en las mujeres (Pérez-Chuecos, 2017). También se encontró que el tipo de contrato influye en la CVL (Uribe-Rodríguez et al, 2011); de manera puntual, los contratos fijos o indefinidos se asocian a mayor compromiso y los temporales se relacionan con inestabilidad laboral (González et al, 2014).…”
Section: Calidad De Vida Laboral Y La Autoeficacia Profesional: Relac...unclassified